The Role of the Village Head in Mediation of Land Issues for Investment in the Construction of a Medical Waste Treatment Plant: A Case Study in Pengambengan Village - I Ketut Widia (Fakultas Hukum, Universitas Warmadewa, 2022)
The dynamics of rejection of development as a large-scale investment almost always occurs and is carried out by some people. Likewise, when there is an issue of the construction or investment of a medical waste treatment plant in Pengambengan Village, immediately there are people who reject it in various ways and reasons. Indeed, there is often a distortion between the needs of the community and the wishes of investors. Therefore, it is necessary to have the ability of community leaders, religious leaders, especially the Village Head to be able to manage this land-based investment conflict properly, respectfully, and elegantly. The purpose of this study was to identify and understand the mediation technique carried out by the Village Head of Pengambengan and to understand the challenges and obstacles to the construction of a medical waste factory in Pengambengan Village. The theory used to analyze the problem is the theory of legal protection and the theory of salus populi supreme lex (public safety is the highest law). The research method used is qualitative legal research or sociological research. Presentation of data using a systematic description technique. The conclusion of this research is, The solution that is expected to be used to solve this problem is mediation in order to reach consensus between investors and the community. The last technique in conducting mediation is to ratify the agreed agreement, then carry it out according to what has been agreed. The inhibiting factor for this investment is public understanding, which still needs to be improved. While the supporting factors are, Pengambengan Village is indeed a special area for industry and this investment can improve the welfare of the community because it absorbs a lot of workers.